Healthy Sisters: A Feasibility study of a health behavior intervention for women of color breast cancer survivors. Issue 5 (3rd September 2018) - Knobf, M. Tish; Erdos, Diane; Jeon, Sangchoon
ABSTRACT: There is strong evidence for the need to educate and empower women of color breast cancer survivors (WCBCS) to adopt healthy lifestyle behaviors. The purpose of this study was to explore feasibility and preliminary efficacy of a culturally grounded lifestyle intervention on functional ability, quality of life, and health behaviors. A community-based sample of WCBCS was recruited from two inner cities, with encouragement to invite a partner. There were 30 WCBCS and 10 partners who participated in the 6-week interactive intervention. Data were collected at baseline, end of intervention and 3 and 6 months. There was significant improvement in healthy lifestyle behaviors ( p = 0.041), physical activity ( p = 0.003), nutrition ( p = 0.007), and stress management ( p = 0.010) for WCBCS and, for partners, improvements in healthy lifestyle behaviors ( p = 0.041), nutrition ( p = 0.007), and health responsibility ( p = 0.034).